2021
DOI: 10.24843/ljlc.2021.v12.i02.p03
|View full text |Cite
|
Sign up to set email alerts
|

Encourage Students’ Affective Value in EFL Class Through Cooperative Learning

Abstract: In this modern era, education is required not only to be able to create intelligent students but also to be able to create students who have good attitudes. The attitude that is needed when they are in the midst of society. Such as tolerance, respect for the opinions of others, mutual cooperation and the others. Considering that these attitudes have begun to decrease by the times and the advancement of civilization. Therefore, an educator is expected to be able to develop the ability of students not only in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Other studies also suggest that cooperative learning significantly influences students’ social development (Johnson et al, 2014; Lou et al, 2006; Yanti, 2021), interactions with other group members, and their respect for the assignment contributions of others (Gillies, 2016). Moreover, studies show that cooperative learning in an EFL classroom improves students’ working relationships, class involvement, achievement (Gillies, 2016; Yanti, 2021), solidarity, respect and tolerance (Rabi’ah et al, 2021). Similarly, a study conducted by Neo et al (2012) showed that students who engaged in cooperative learning recognized the need for respect, communication, sharing, and tolerance as essential components of collaboration and the project’s success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also suggest that cooperative learning significantly influences students’ social development (Johnson et al, 2014; Lou et al, 2006; Yanti, 2021), interactions with other group members, and their respect for the assignment contributions of others (Gillies, 2016). Moreover, studies show that cooperative learning in an EFL classroom improves students’ working relationships, class involvement, achievement (Gillies, 2016; Yanti, 2021), solidarity, respect and tolerance (Rabi’ah et al, 2021). Similarly, a study conducted by Neo et al (2012) showed that students who engaged in cooperative learning recognized the need for respect, communication, sharing, and tolerance as essential components of collaboration and the project’s success.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cooperative language learning empowers EFL learners to be brave enough to speak in the target language by offering a democratic, peaceful and nonthreatening setting (Zhou, 2012). It increases solidarity, respect, and tolerance (Rabi'ah et al, 2021) and enhances student working relationships, social skills, and class participation (Yanti, 2021). A further study conducted by Awada and Gutie´rrez-Colo´n (2019) proved that cooperative learning through blogs helps reduce students' apprehension about intercultural communication.…”
Section: Recent Studiesmentioning
confidence: 99%